High accuracy ultrasonic monitoring of electrochemical processes - Zou,F; Cegla (Electrochemistry Communications, 2017)
Ultrasonic testing (UT) can be used for non-intrusive corrosion monitoring. In this paper, we firstly show that UT is not only capable of monitoring wall-thickness losses, but can also be exploited for tracking electrodeposition processes. All ultrasonic measurements reported are in agreement with analytical predictions and optical surface profile measurements. Since UT is highly sensitive to the coupling conditions and the relative acoustic properties of substrates and deposited materials, it can become an effective tool for studying the interface phenomena in which dissolution and deposition compete. Examples of these include passivation layer formation and scale deposition which are corrosion-inhibiting electrochemical processes.